The impact of shelf life on exposure as revealed from quality control data associated with the quargel outbreak - Wagner, Martin; Skandamis, Panos; Allerberger, Franz; Schoder, Dagmar; Lassnig, Caroline; Müller, Mathias; Rychli, Kathrin (International journal of food microbiology, 2018)
A cluster of 34 human cases of listeriosis was traced to consumption of contaminated quargel cheese, a sour milk specialty sold in Austria, Germany and Czech Republic. Here, we try to assess how many portions were consumed by the Austrian population at a certain contamination level (CL). In total, 1623 cheese lots were produced during the outbreak period resulting in >3 million portions of cheese delivered to the market. From 650 sets of quality control data provided by the food business operator, we reconstructed the contamination scenario over time and identified 84 lots that were found to be positive. With regard to another sixteen lots, a CL was found ranging from one to 3,84 log10 CFU L. monocytogenes/g, measured in product stored between one to 23 days after production. However the number of storage days at home before consumption is unknown. To resolve this issue, we modelled the theoretical CL of the product if consumed either 20, 30, 40 or 50 days post production. We found that 10 lots (approx. 27,350 portions) would have been contaminated at CLs higher than 3 log10 CFU L. monocytogenes/g if all cheese had been consumed after 20 days of storage. This number shifts to 20 lots (approx. 54,700 portions) after 30 days of storage. If all cheese had been consumed at the end of shelf life (50 days of storage), theoretically 242,5 lots would have exceeded a CL of 6 log10 CFU L. monocytogenes/g. We concluded that the extended shelf life given to the product was a driver of the outbreak scenario. It is stunning to note that so few cases were reported in spite of consumers' massive exposure to L. monocytogenes. We hypothesized that a low pathogenicity of both quargel outbreak clones (QOC1 and QOC2) could have contributed to this discrepancy. Our hypothesis was falsified since both strains QOC1 and QOC2 are fully virulent in an oral infection mouse model, showing even higher pathogenicity than the reference strain EGDe.
Keywords: Virulence; Animals; Food Microbiology; Germany; Listeria monocytogenes; sýr; Female; Contamination scenario; ženské pohlaví; Rakousko; řízení kvality; Food Contamination; lidé; Austria; Mice; Německo; Aged, 80 and over; Mice, Inbred BALB C; Cheese; Exposure; myši; Milk; virulence; potravinářská mikrobiologie; kontaminace potravin; retrospektivní studie; Disease Outbreaks; Male; Quality Control; Aged; Czech Republic; myši inbrední BALB C; Česká republika; lidé středního věku; epidemický výskyt choroby; senioři nad 80 let; senioři; zvířata; mužské pohlaví; mléko; Retrospective Studies; Middle Aged; Listeriosis; Pathogenicity; listeriové infekce; Humans